Constrained Minimum Variance Portfolio Considering Investors’ Environmental, Social, and Governance Preferences - Kumagai, Satoshi; Fujii, Ryusei (International Journal of Economics and Financial Issues, 2025)
Environmental, social, and governance (ESG) investing incorporates ESG factors into the investment decision-making process. By screening for companies with strong ESG practices, investors can potentially achieve long-term value growth and reduce the risk of corporate misconduct. In ESG investing, portfolio managers use a screened universe of stocks to construct portfolios based on financial risk and returns. At this point, the extent to which ESG factors are reflected in the portfolio allocation ratios becomes a black box. This study proposes a method for constructing an ESG portfolio that considers investors’ ESG preferences. Investors’ perceived importance of ESG is quantified using a hierarchical decision-making method. This measure is then applied as a constraint condition to determine stock investment ratios by solving a risk minimization problem. For a universe of 50 stocks, the Sharpe ratio of the constrained portfolio considering investors’ ESG preferences was higher than that of the unconstrained portfolio.